Examination of General Nutritional Habits of Students of Niğde Ömer Halisdemir University, Academy of Pyhsical Education and Sports - İbrahim Ümran Akdağcık; Meryem Altun (Selcuk University, 2018)
The purpose of this study is to examine the general nutritional habits of students studying at Niğde Ömer Halisdemir University, School of Physical Education and Sports. Through voluntary participation -as being 89 males and 94 females- 180 students in total. General Nutrition Scale whose reliability has been realized by Öztürk (2017) had been used as data collection tool. In the analysis of data, percentage and frequency had been used for demographical features, and ANOVA had been used for descriptive statistics and for the determination of differences among groups. Consequently, while a significant difference had been determined in between the variable of age and the propositions regarding attitudes towards general nutrition, and in between the variables of gender, height and weight and the propositions regarding behaviors towards food supplements. In the propositions regarding behaviors towards food supplements, it had been determined that the averages are high in favor of males. While a significant difference had been determined in the variable of department and in propositions regarding attitudes towards general nutrition. In the propositions regarding attitudes towards general nutrition, it had been determined that it is in favor of the students of Department of Coaching from among the students of Department of Coaching and students of Department of Sports Management. While a significant relation in positive direction had been determined in between the variable of weekly attendance to gym and propositions regarding behaviors towards additive containing nutrition. It has been revealed that the individuals attending the gym exhibit a more positive attitude regarding the use of additive containing substances compared to the ones not attending the gym. While a significant relation in positive direction had been determined in between the variable of number of meals and propositions regarding behaviors towards additive containing nutrition, no significant relation had been found among the other propositions.